Variations on gui and the Trouble with Ghosts in Modern Chinese Fiction - Imbach, Jessica (Asiatische Studien, 2016)
Ghosts appear in a great number of fictional works from the early modern period to the present. Yet, to this date no systematic study of this very heterogeneous textual corpus has been undertaken. This paper proposes as a useful starting point a review of figures and discourses of spectrality, mainly in Republican-era literary and critical texts, that focuses in particular on the different meanings and usages of the term , “ghosts”. A better understanding of helps us not only to distinguish different approaches towards spectral figures, which do not necessarily always operate on a secular-religious binary, but also brings the entangled dynamics of the aesthetic and the political in modern Chinese ghost fiction into sharper focus.